2020
DOI: 10.2147/ceg.s256627
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiologic Study of Gastric Cancer in Iran: A Systematic Review</p>

Abstract: Background Gastric cancer (GC) is one of the most common cancers in Iran. Knowledge of the epidemiology of the disease is essential in planning for prevention. So this study aimed to investigate the epidemiological aspects of gastric cancer including prevalence, incidence, mortality, and risk factors of Iran. Methods This systematic review study was based on articles published in both English and Persian languages during the years of 1970–2020 in international databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 186 publications
0
25
0
Order By: Relevance
“…Moreover, there was a link between dairy products, processed red meat, fruit juice, legumes, smoked and salty fish, salt, strong as well as hot tea consumption with the risk of stomach cancer. There was also an inverse link between fresh fruit, citrus, and garlic consumption and stomach cancer ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there was a link between dairy products, processed red meat, fruit juice, legumes, smoked and salty fish, salt, strong as well as hot tea consumption with the risk of stomach cancer. There was also an inverse link between fresh fruit, citrus, and garlic consumption and stomach cancer ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, mortality from GC can be the first leading factor of death due to cancer in both sexes 8 . However, the incidence of the disease was higher in men than in women 9 . Considering the low rate of 5-year survival of GC patients, identification and control of predictive factors remain the essential prevention methods 10 .…”
Section: Introductionmentioning
confidence: 88%
“…Epidemiologic studies showed that the prevalence of gastric cancer in different provinces of Iran is between 0.2 and 100 per 100 000. 1 Although the incidence of gastric cancer has been decreased worldwide in recent decades, however it is the most common cancer in some provinces of Iran such as north and northwest provinces. 2 Unlike colon cancer, there has not been significant increase in survival of the patients with gastric cancer, and it is still the second leading cause of cancer related deaths.…”
Section: Introductionmentioning
confidence: 99%